Tularemia in Children, Turkey, September 2009–November 2012 - Tezer, Hasan (Emerg Infect Dis, 2015)
Tularemia, a zoonotic disease caused by Francisella tularensis, is found throughout most of the Northern Hemisphere. It is not well known and is often misdiagnosed in children. Our aim with this study was to evaluate the diagnosis, treatment, and prognosis for 100 children with tularemia in Turkey. The mean patient age was 10.1 ± 3.5 years (range 3–18 years), and most (63%) patients were male. The most common physical signs and laboratory findings were cervical lymphadenopathy (92%) and elevated erythrocyte sedimentation rate (89%). Treatment response was higher and rate of relapse lower for children 5–10 years of age than for those in other age groups. Associated with treatment failure were female sex, treatment delay of ≥16 days, and use of doxycycline. Tularemia is endemic to Turkey, and the number of cases has been increasing among children as well as adults.